Review paperEndovascular repair of thoracic aortic aneurysm - Akin, Ibrahim; Kische, Stephan; Rehders, Tim C.; Nienaber, Christoph A.; Rauchhaus, Mathias; Ince, Hüseyin (Archives of Medical Science, 2010)
A thoracic aortic aneurysm (TAA) is a potentially life-threatening condition with structural weakness of the aortic wall, which can progress to arterial dilatation and rupture. Today, both an increasing awareness of vascular disease and the access to tomographic imaging facilitate the diagnosis of TAA even in an asymptomatic stage. The risk of rupture for untreated aneurysms beyond a diameter of 5.6 cm ranges from 46% to 74% and the two-year mortality rate is greater than 70%, with most deaths resulting from rupture. Treatment options include surgical and non-surgical repair to prevent aneurysm enlargement and rupture. While most cases of ascending aortic involvement are subject to surgical repair (partially with valve-preserving techniques), aneurysm of the distal arch and descending thoracic aorta are amenable to emerging endovascular techniques as an alternative to classic open repair or to a hybrid approach (combining debranching surgery with stent grafting) in an attempt to improve outcomes.